Real cities: modernity, space and the phantasmagorias of city life / Steve Pile. - Pile, Steve, 1961- (SAGE, 2005)
'Real Cities' shows why it is necessary to take seriously the more imaginary and emotional aspects of city life. Drawing on the work of Walter Benjamin, Freud and Georg Simmel, it conducts an empirical investigation into the dreamlike and ghost-like experiences - phantasmagoria - of the city.